We have [tex]x^{-n} = \frac1{x^n}[/tex] if [tex]n[/tex] is a positive integer and [tex]x\neq0[/tex], as well as [tex]x^0 = 1[/tex] if [tex]x\neq0[/tex]. So right away we can simplify to
[tex]\left(x^{-1} y^2\right) \left(-3 x^2 y^0\right) = \left(\dfrac{y^2}x\right) \left(-3x^2\right) = -\dfrac{3x^2y^2}x[/tex]
If [tex]x=0[/tex], then the starting expression is undefined. So we accept that [tex]x=0[/tex], in which case [tex]\frac xx = 1[/tex], and the overall expression simplifies to
[tex]\left(x^{-1} y^2\right) \left(-3 x^2 y^0\right) = \boxed{-3xy^2}[/tex]